Research on Architectural Design Technology of Macau World Heritage Building Mandarin’s House in Response to Hot and Humid Climate - Yile Chen; Junzhang Chen; Liang Zheng (PT FORMOSA CENDEKIA GLOBAL, 2022)
The climate of Lingnan determines the form of the building. As a well-preserved representative building in the world cultural heritage of Macau with the characteristics of Lingnan architectural style, the Mandarin’s House reflects the architectural design of the subtropical zone and the humid and hot climate of Macau, which is worthy of later analysis, study and research application.